Feed-Forward Approach in Stator-Flux-Oriented Direct Torque Control of Induction Motor with Space Vector Pulse-Width Modulation - Klzilkaya, Muhterem Ozgur; Gulez, Kayhan (SPRINGER HEIDELBERG, 2016)
Two major obstacles in the utilization of electrical vehicles are their price and range. The collaboration of direct torque control (DTC) with induction motor (IM) is preferred for its low cost, easy implementation, and parameter independency. However, in terms of edges, the method has drawbacks, such as variable switching frequency and undesired current harmonic distortion. These drawbacks result in acoustic noise, reduced efficiency, and electromagnetic interference. A feed-forward approach for stator-flux-oriented DTC with space vector pulse-width modulation is presented in in this paper. The outcome of the proposed method is low current harmonic distortion with fixed switching frequency while preserving the torque performance and simple application feature of basic DTC. The method is applicable to existing and forthcoming IM drive systems via software adaptation. The validity of the proposed method is confirmed by simulation and experimental results.
Keywords: Direct torque control; Feed-forward control; Flux linkage ripple; Space vector pulse-width modulation; RIPPLE REDUCTION; LOSS-MINIMIZATION; HIGH-PERFORMANCE; CONTROL STRATEGY; IMPLEMENTATION; SCHEME; ALGORITHM; ENERGY; DTC; Engineering